Colocalization of P450 Aromatase and Oxytocin Immunostaining in the Rat Hypothalamus - El-Emam Dief, A.; Caldwell, J. D.; Jirikowski, G. F. (Hormone and Metabolic Research, 2013)
With combined immunoperoxidase and immunofluorescence, we observed colocalization of cytochrome P450 aromatase with the posterior lobe peptide oxytocin and its associated neurophysin 1 in adult male rats. P450 was most abundant in the anterior hypothalamus. Colocalization of OT with P450 was observed in the preoptic region, the periventricular nucleus of the hypothalamus, the lateral subcommissural nucleus, and in the zona incerta. Magnocellular perikarya in the supraoptic and in the paraventricular nuclei contained only occasionally both antigens. P450 immunostaining overlapped to a great extent with known estrogen target regions. Oxytocinergic functions are controlled by estradiol while androgen receptors are mostly absent in neuroendocrine hypothalamic nuclei. Our findings suggest that systemic androgens may be aromatized to estrogens in male oxytocinergic neurons linked to the limbic system.
Keywords: hypothalamus; androgens; oxytocin; aromatase; limbic system; pituitary